A multi-body dynamics based numerical modelling tool for solving aquatic biomimetic problems. (3rd July 2018) - Li, Ruoxin; Xiao, Qing; Liu, Yuanchuan; Hu, Jianxin; Li, Lijun; Li, Gen; Liu, Hao; Hu, Kainan; Wen, Li
Abstract: In this paper, a versatile multi-body dynamic algorithm is developed to integrate an incompressible fluid flow with a bio-inspired multibody dynamic system. Of particular interest to the biomimetic application, the algorithm is developed via four properly selected benchmark verifications. The present tool has shown its powerful capability for solving a variety of biomechanics fish swimming problems, including self-propelled multiple degrees of freedom with a rigid undulatory body, multiple deformable fins and an integrated system with both undulatory fish body and flexible fins. The established tool has paved the way for future investigation on more complex bio-inspired robots and live fish, for either propulsion or manoeuvring purposes.